Development of Innovative Strategies to Promote the Growth of Entrepreneurships in the Canton Sucre, Province of Manabí, Ecuador - Manuel , Roman Velez Victor; Carmen , Ormaza Esmeraldas Elizabeth Del; Alberto , Romero Zambrano Miguel; Mar , Hidalgo Cedeño Maria Del; Humberto , Chica Gilces Edgar; Leonardo , Centeno Martinez José (Journal of Ecohumanism, 2024)
Sucre is one of the cantons that make up the Province of Manabí in Ecuador, the socioeconomic development of this region has been based on tourist activities, which its inhabitants develop through various types of companies, within which Hotels are located. , shops big, smalland other types of services or benefits that have arisen from the figure of entrepreneurship, that is, those initiatives that are not considered as companies because they lack formality and commercial registration. Due to the aforementioned, the development of this research has been proposed with the objective of knowing thedevelopment of innovative strategies to promote the growth of businesses in the Sucre canton, Manabí Province, Ecuador. The methodology used is quantitative, a data collection instrument was designed with eight (8) items which had closed Yes/No responses, it was applied in the context of the entrepreneurs of the Canton Sucre, that is, only the entrepreneurs of the Canton of Sucre were considered. this region. The results were that entrepreneurs know the definition of the activity they practice in its entirety and use strategies in a non-technical way. However,54% with their level of knowledge about the activities they carry out is sufficient to provide a quality service in the various ventures they carry out, only 46% expressed the relevance of this element, which is the training and development of strategies for growth. of its economic activity, as well as of the region. It is concluded that it is necessary to create campaigns to promote legal instruments and training means on innovation and technical training required by development areas.